2002
DOI: 10.4049/jimmunol.169.9.4998
|View full text |Cite
|
Sign up to set email alerts
|

Murine Neonatal CD4+ Lymph Node Cells Are Highly Deficient in the Development of Antigen-Specific Th1 Function in Adoptive Adult Hosts

Abstract: It is well established that murine neonates are biased toward Th2 responses. Th2-dominant responses are observed following immunization with a variety of Ags, using different carrier/adjuvant systems, and are seen in both BALB/c and C57BL/6 mice. Therefore, Th2 skewing appears to be a universal phenomenon unique to the neonatal period. One important question about this phenomenon is whether these responses are due to T cell intrinsic properties or are regulated by the neonatal environment. Here we have address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 51 publications
5
40
0
Order By: Relevance
“…6), is consistent with this idea. Moreover, we recently reported (Adkins et al, 2002) that intrinsic properties of neonatal T cells contribute to Th2-skewing in vivo; in adoptive adult hosts, neonatal lymph node CD4 þ cells were highly deficient in the development of Th1 function. How might these functional differences between neonatal and adult CD4…”
Section: Discussionmentioning
confidence: 99%
“…6), is consistent with this idea. Moreover, we recently reported (Adkins et al, 2002) that intrinsic properties of neonatal T cells contribute to Th2-skewing in vivo; in adoptive adult hosts, neonatal lymph node CD4 þ cells were highly deficient in the development of Th1 function. How might these functional differences between neonatal and adult CD4…”
Section: Discussionmentioning
confidence: 99%
“…Newborns are especially prone to infections for which cell-mediated immunity is protective (1,3). Neonates and infants also have a reduced or suboptimal capacity to mount an effective cell-mediated immunity in response to most vaccines (1,(3)(4)(5). However, introducing a vaccine Ag into the cytoplasm of APCs induces a significant CD8 CTL response even in neonates (3,6,7).…”
Section: Induction Of Protective Immunity Tomentioning
confidence: 99%
“…However, introducing a vaccine Ag into the cytoplasm of APCs induces a significant CD8 CTL response even in neonates (3,6,7). Contrary to the induction of CTLs, Th1 (IFN-␥ producing) CD4 T cell responses have not only been difficult to induce in the neonate, but appear even more difficult to sustain (4,5,8,9).…”
Section: Induction Of Protective Immunity Tomentioning
confidence: 99%
“…Antibody responses in infants were thought to be dominated by IgM due to inadequate function of helper T cells, thus making the antigen-specific B cells unable to undergo isotype switching and hypermutations [24,25]. T cell responses induced by neonatal immunization are indeed lower than in adults [26,27] and development of neonatal CD4 + Th1 functions is severely impaired [28]. However, it has been demonstrated that significant IgG responses may be induced after immunization with protein antigens (reviewed in [23]), indicating that T cell help to promote isotype switch of B cells from IgM to IgG is present already in the neonatal period of life.…”
Section: Introductionmentioning
confidence: 99%